Aggressiveness of Breast Carcinoma in Young Pre-Menopausal Patients - Remisha Zahid Shah, Zahid Mehmood Akhtar, Safeena Sarfraz, Syed Hassan Raza Bokhari, Nazia Noor, Attia Lateef (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Breast cancer is the most commonly diagnosed malignancy in female population. Aim: To determine and compare the frequency of aggressiveness of breast cancer in pre and post-menopausal patients. Study design: Cross sectional study Place and duration of Study: Department of Histopathology, K.E. Medical University Lahore from 1st January 2016 to 31st December 2018. Methodology: One hundred and fifty female patients diagnosed with breast cancer to assess the aggressiveness of breast cancer in young - premenopausal patients. Post-Surgical Modified Radical Mastectomy specimens were submitted and evaluated for grade, stage, involved lymph nodes, tumor size and metastasis. Results: Sixty four percent of the tumors were left sided and the invasive ductal carcinoma was the most dominant histologic type (96%). Ninety two patients were premenopausal while 58 were post-menopausal. Nodal positivity in patients less than 40 years was more pronounced (74.2% versus 56.8%, p=0.029). Conclusion: Young premenopausal patients represent high risk group for advanced breast cancer.